Modeling Regional Elderly Employment Due to Seasonal Fluctuation in Tomsk Region; Innovation Management and Education Excellence Vision 2020: from Regional Development Sustainability to Global Economic Growth - Barysheva G. A. Galina Anzelmovna; Filippova T. V. Tatiana Vasilievna; Baryshev A. A. Aleksey Andreevich; Aksenova Yu. V. Yuliya Viktorovna (2016, 2016)
Title screen